ANALYSIS OF THE INTERNAL CONTROL SYSTEM OF TRADE GOODS INVENTORY AND ACCOUNTING IMPLEMENTATION AT PT. SAMA ELOK - Ningsih, Eka Wati; Suroso, Suroso; Arnita, Vina (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The purpose of this research was to find out how the internal control system of the merchandise supply in PT. Equally Good and whether the company's policy on recording and valuing merchandise inventory is in accordance with PSAK No. 14. The analysis method used in this study is descriptive method. The results of this study show that the system of internal control using the trading supply information system is that this trading supply information system makes the procedures and activities performed by the company faster and faster. The process of calculating the goods can be computerized and the results of the calculations given are faster and more accurate. Trademark stock data may be provided on a timely basis with the design of this design information as this data is updated automatically at each transaction of receipt and expenditure. The availability of this design information system enables the Director to monitor the performance of the merchandise section of the merchandise inventory reports. The simulation results of the amount of time it takes for the process of providing merchandise using this design information system results in a saving of 75 minutes from the initial system. PSAK No. 14 companies have implemented well. This can be seen from the logging system and the inventory valuation method has been carried out in accordance with accounting principles.